Characterization of mechanical properties and fracture mode of additively manufactured carbon fiber and glass fiber reinforced thermoplastics - Goh, Guo Dong (2019)
Continuous fiber-reinforced polymer (FRP) composites have been used for many applications to create strong yet lightweight products due to their high strength-to-weight and stiffness-to-weight ratios. Aerospace [1], automotive [2], and sport [3]industries are three of the few industries that have been using FRP composites. The increasing need for prototyping and customization of fiber reinforced polymer composite parts is prompting innovations in new manufacturing processes to realize short manufacturing cycle time and low production cost, which is challenging to accomplish using conventional molding process. Fused filament fabrication (FFF) - a material extrusion additive manufacturing (AM) technique trademarked as fused deposition modelling (FDM) by Stratasys- holds promise to achieve low-cost production on continuous fiber-reinforced thermoplastic (FRTP) composites. In this paper, the FFF technique is employed to fabricate continuous carbon and glass FRTP composites and its microstructural characteristics and the resulting tensile, flexural, and quasi-static indentation characteristics of the printed composites are examined. Additionally, the fracture behavior of each test sample is evaluated and discussed in detail.